Clients' Retrospective Accounts of Corrective Experiences in Psychotherapy: An International, Multisite Collaboration. Issue 2 (23rd November 2016) - Constantino, Michael J.; Angus, Lynne
Abstract : This article introduces a series of 4 original research reports that used varied qualitative methods for understanding an internationally diverse sample of clients' own accounts of corrective experiences (CEs), as they looked back on their completed psychotherapy. The basis for all studies, which were conducted across 4 different countries, was the Patients' Perceptions of Corrective Experiences in Individual Therapy (PPCEIT) semistructured interview protocol (Constantino, Angus, Friedlander, Messer, & Moertl, 2011). The PPCEIT interview assesses clients' retrospective accounts of aspects of self, other, and/or relationships that may have been corrected, and what they perceived as corrective experiences that facilitated such transformations. It also asks for specific, detailed examples of these accounts and experiences. Across all studies, the PPCEIT interview generated rich clinical material and resulting empirically generated themes that may inform clinical practice. After briefly defining the CE construct and highlighting a lack of research on clients' own accounts of such experiences, we describe the development of the PPCEIT interview (and provide the full interview manual and question protocol as appendices). We then summarize the foci of the culturally diverse reports in this series.